Adaptability and behaviour stability of corn cultivars at thirteen environments of Brazilian Northeast coastal tableland - Santos, Manoel Xavier dos; Leal, Maria de Lourdes da Silva; Pacheco, Cleso Antonio Pato; Tabosa, José Nildo (Pesquisa Agropecuaria Brasileira, 1999)
The potential of the Brazilian Northeast coastal tablelands for corn production and the adaptability and stability of sixteen corn cultivars were evaluated at thirteen environments of this region in 1994/95 on a randomized block design experiment with three replications. The large potential of this coastal strip for corn production was evidenced by the obtained yield, highlighting the hybrids, on the coastal tablelands of Piauí, Sergipe and Bahia States, where corn would become a major crop option for the growers. Pooled variance analysis showed significant difference for environments and cultivars, and the interactions environment x cultivar, which were inconsistent. Hybrids had better adaptation than varieties and populations; they are recommended for higher input situations. The AG 510 hybrid showed good adaptation to low and high input conditions, and therefore is recommended for both situations. The BR 5011, BR 5028, BR 106 and BR 5033 varieties had reasonable yields and are suitable for small and medium corn growers.